Potential Development of Small Modular Reactor (SMR) In the Application of Nuclear Energy Sources in Indonesia - Iqbal, Muh; Marlen, Liany; Melati, Rima; Nurhasmi (Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, 2025)
This article analyzes the development potential of a Small Modular Reactor (SMR) as a solution energy transition in Indonesia to reduce dependence on fossil fuels, especially oil and coal. Through a literature review, the article compares SMR performance with Generator Electricity Steam Power (PLTU) in terms of energy capacity, impact, and additional applications such as water desalination and hydrogen production. The results showed that the fourth generation SMRs (HTGR, MSR) have high-efficiency electricity, more tall 40-50%, compared to Steam Power Plant (30-40%), with low carbon (3,676-5,388 g CO2 equivalent/kWh for SMR and 1,000 g CO2 /kWh for PLTU). SMR is also capable of producing desalinated water at the lowest cost (USD 0.398/m3 or Rp 6,574/m3) and sustainable hydrogen (9.63 g/kWh). However, adoption of SMR in Indonesia faces complex challenges, including high FOAK costs, regulations that are not yet adaptive, limited supply of special fuels, gaps in skilled human resources, and community resistance regarding waste. Nuclear. This article recommends regulatory revisions, financial incentives based on KPBU schemes, HR training through international collaboration, and public education strategies to increase social acceptance. With integrated policies, SMR has the potential to become a pillar of Indonesia's energy transition towards decarbonization and sustainable energy security.